The Role of Methodological Approaches in Assessing the Effectiveness of Military-Economic Forecasting - Chernyshova, Iryna; Busel, Vitalii (Social Development and Security, 2025)
Purpose. To analyze and systematize methodological approaches to assessing the effectiveness of military-economic forecasting and to determine their content, objectives, and role in the defense planning process under conditions of increased uncertainty in the security environment and limited economic resources of the state.Method. The methodological framework of the study is based on an integrated combination of systemic, scenario-based, comparative, indicative, economic–mathematical, information-analytical, and expert-analytical approaches. The study employs methods of analysis and synthesis, generalization, comparison, modeling, and expert assessment, which makes it possible to consider military-economic forecasting as a complex multifactor system.Findings. The feasibility of applying a multi-level methodology for assessing the effectiveness of military-economic forecasting is substantiated; the role of each methodological approach is defined, and their generalized characteristics are formulated. It is demonstrated that the integration of different approaches makes it possible to enhance the accuracy, timeliness, adaptability, and practical relevance of forecast estimates, as well as to reduce the risks of inefficient use of defense resources.Theoretical implications. Deepening scientific understanding of the effectiveness of military-economic forecasting and the development of methodological foundations for its assessment within the context of the modern military economy. The proposed systematization of approaches provides a basis for the further development of defense forecasting theory.Practical implications. The possibility of using the obtained results in the activities of public administration and defense planning bodies when developing defense programs, formulating budgets, determining priorities for the development of the defense-industrial complex, and improving the system of military-economic forecasting.Future research. The development of integral indicators for assessing the effectiveness of military-economic forecasting, their empirical testing using specific defense programs as case studies, as well as the expanded application of digital and simulation-based modeling tools within the defense planning system.Papertype. Review and analytical.